Keputusan Memilih Jasa Wedding Organizer Berdasarkan Physical Evidence Factor (Studi Kasus pada CV. Anpian Wedding Organizer Ciamis) - Hadiani, Dian; Munawar, Andri Helmi; Supriatna, Nana (Universitas Medan Area, 2019)
The decision process to choose the services of a wedding organizer is already considered an identity and a prestige now. With the number of start-ups engaged in this field that only rely on capital